Competitive Advantage Strategies to Improve the Business Performance of PT. XYZ's Cosmetic Products - Oki Permanakusumah; Faizatun; Deriawan (Jurnal FARMASIMED (JFM), 2025)
This study aims to analyze and formulate a competitive business strategy for PT. XYZ to enhance its corporate performance. The research employs a qualitative descriptive method with a quantitative approach. Primary data were obtained through FGDs and in-depth interviews with ten informants, while secondary data were sourced from literature and company reports. Data processing involved four interrelated methods: the IFE and EFE matrices to analyze internal and external factors, the SWOT, IE, and Grand Strategy matrices to determine alternative business strategies, and the QSPM method to establish strategic priorities. The findings indicate that PT. XYZ's strategies include affordable pricing, product variations, branding, and extensive distribution. Internal and external factor analysis resulted in IFE and EFE scores of 2.60, placing the company in the "Hold and Maintain" quadrant, with a focus on product development and market penetration. The grand strategy matrix positions the company in Quadrant 1, highlighting its potential to capitalize on opportunities through an aggressive business strategy. Competitive analysis identifies PT. Mandom Indonesia as the strongest competitor, with a score of 3.3. The SWOT analysis produced seven key competitive strategies, including optimizing machinery for product innovation, external collaboration, sales system integration, internal coaching, strengthening digital media presence, utilizing locally sourced materials with international quality standards, and adaptive planning for regulatory changes. The highest QSPM score (5.40) was achieved by the strategy of optimizing custom machinery for innovative and hard-to-replicate products. It is recommended to maintain the existing strategy, monitor performance, and continuously innovate.